INTERPERSONAL METAPHOR IN “INDONESIA NOW” ENGLISH NEWS TV PROGRAM - Desi Kristina Purba; Siti Aisyah Ginting; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2018)
ABSTRACTThis study investigates interpersonal metaphor in “Indonesia Now” English news TV program based on Systemic Functional Linguistics approach. The objective of the study are to identify what types of interpersonal metaphors in “Indonesia Now”, to describe how those interpersonal metaphors are used, and to explain in what context those interpersonal metaphor are used. A qualitative descriptive research design was used in this study. The data were taken from one weekly broadcast Indonesia Now in January to June 2017. The data were collected by recording the “Indonesia Now” program on Metro TV, then transcribing the program broadcasts into written text, classifying the data into types of interpersonal metaphors and then drawing conclusion from the data. The findings of the study show that there are five types of interpersonal metaphor used in “Indonesia Now”, namely metaphor of mood, modality, epithet, euphemism, and connotation. The use of interpersonal metaphor in “Indonesia Now” is realized by use of incongruent types of expressing meaning in interaction. In addition, the use of interpersonal metaphor, it is also found that expressing emotion as the new findings of this study which not in line with the previous theories. The speaker use interpersonal metaphor to accurately reflect their point of view and express the emotion and this purpose can be achieved with the reference to social context which named context of situation. Keywords: Interpersonal Metaphor, Systemic Functional Linguistic, Indonesia Now